Combined effects of biocontrol agents and soil amendments on soil microbial populations, plant growth and incidence of charcoal rot of cowpea and wilt of cumin - Vijeta SINGH; Ritu MAWAR; Satish LODHA (Phytopathologia Mediterranea, 2012)
Field experiments were conducted for 2 years to determine the effectiveness of combined use of two biocontrol agents, Bacillus firmus and Aspergillus versicolor for control of Macrophomina phaseolina induced charcoal rot of cowpea and Fusarium oxysporum f. sp. cumini induced wilt of cumin. The lowest level of plant mortality (3‒4%) due to charcoal rot of cowpea was recorded when bacterium coated seeds were sown in radish compost amended soil compared to the non-amended soil (13.8‒20.5%), but this was not significantly better than some other treatments. Cowpea roots from B. firmus coated seeds had better nodulation than any of the individual A. versicolor treatments. Although B. firmus coated seeds + A. versicolor + farmyard manure resulted in maximum nodulation this was not significantly different to B. firmus seed coating. Root colonization by the combined biocontrol agent treatments was better than the individual biocontrol agent treatments. Combining A. versicolor with farmyard manure supported the maximum populations of total fungi and actinomycetes. In both winter seasons, the lowest incidence of wilt (1.0‒5.2%) on cumin was recorded when A. versicolor was amended with neem compost compared to the non-amended soil (5.7‒10.5%). Maximum colonization of A. versicolor on roots was observed in B. firmus + A. versicolor + farmyard manure amended plots. During both years, the treatment combination of A. versicolor in neem compost amended plots resulted in maximum populations of fungi, bacteria and A. versicolor in the soil, which was greater than in the non-amended soil. Significant increases in disease control were not recorded after single or repeated delivery of A. versicolor. These results suggest that combining B. firmus as seed coatings with A. versicolor as soil applications gives improved control of M. phaseolina and Fusarium induced diseases on legume and seed spice crops in arid soils.